Investment linked takaful plan patronage:evidence from Malaysia - Parveen, Tamiza; Razali, Siti Salwani; Che Mohd Salleh, Marhanum (Faculty of Islamic Economics and Business State Islamic University (UIN) Sunan Kalijaga, 2019)
Investment-linked Takaful is a recent innovation introduced in Malaysia. This study focuses on Investment-linked takaful plan selection in Malaysia. We have used a selfadministered questionnaire to collect data from 143 respondents from the Klang Valley area. Data collected through the survey was analyzed through descriptive statistics, correlation and regression analysis. Results indicate that fee payment and benefits play a significant role in Takaful operator selection while coverage and benefits affect the investment-linked product selection in Malaysia. This study is unique as it provides empirical evidence on the investmentlinked takaful investment which is limited in supply. Results provided by this study can be useful for takaful operators in designing the most appropriate investment-linked product for attracting customers